Growth strategies of Li7La3Zr2O12 electrolytes for Li-ion thin film battery - Jitendra Pal Singh; Anil K Paidi; Sangsul Lee (Chemical Engineering Journal Advances, 2023)
This work depicts the recent progress towards utilizing several methods to grow Li7La3Zr2O12 (LLZO) thin film electrolytes of Li-rechargeable batteries. The composition, crystalline phase, and Li-ion conductivity of the electrolyte are affected by the pre and post synthesis processing and synthesis method. The properties of the target material used to deposit SSE thin films also affect the nature of the electrolyte. Thus, this review article depicts the synthesis of bulk SSE and the various deposition methods for growing thin films of SSE. The strategies used for optimizing the conductivity of bulk (target) and thin-film forms are elaborated. In the case of bulk/target, doping/codoping, synthesis methodology are effective approaches for optimizing the conductivity of LLZO. However, advanced tools such as co-sputtering and a combination of multiple deposition methods are utilized to optimize the conductivity of LLZO thin films. Growth of LLZO in the form of a multilayer structure has also been an effective approach for controlling ionic conductivity. Apart from these reported approaches, we propose that doping by ion implantation might be a promising strategy to control the conductivity of grown SSE.